ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS IX PADA MATERI PERSAMAAN KUADRAT DI SMP NEGERI 3 TUALANG - Muhammad Iqbal; Aniswita Aniswita; Sonny Hutabarat (Universitas Pahlawan Tuanku Tambusai, 2022)
This study discusses problems related to overcoming students' difficulties incarrying out learning activities. The purpose of this study is to explain and provide resultsof appropriate learning action solutions for students who experience difficulties in learningmathematics. The implementation of this research utilizes a literature review. The object of the research was carried out in class IX at SMPN 3 Tualang on the grounds that thereare still many students at that school who have learning difficulties. Data collection techniques with observation, tests, and documentation. The results stated that after implementing the discovery learning model of action, students' learning difficulties could be overcome properly. For this reason, the actions taken have an influence on the problem of student learning difficulties. Keywords: Learning Difficulty, Discovery Learning, Quadratic Equation